2006
DOI: 10.1017/s0022112006000309
|View full text |Cite
|
Sign up to set email alerts
|

Standing and travelling waves in cylindrical Rayleigh–Bénard convection

Abstract: The Boussinesq equations for Rayleigh-Bénard convection are simulated for a cylindrical container with an aspect ratio near 1.5. The transition from an axisymmetric stationary flow to timedependent flows is studied using nonlinear simulations, linear stability analysis and bifurcation theory. At a Rayleigh number near 25 000, the axisymmetric flow becomes unstable to standing or travelling azimuthal waves. The standing waves are slightly unstable to travelling waves. This scenario is identified as a Hopf bifur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 43 publications
4
22
0
4
Order By: Relevance
“…The latter would correspond to those studied in the half-zone model 46 and discussed in detail in the Rayleigh-Bénard configuration. 47 In both studies the initial standing waves, which result from superposition of the rotating waves traveling in opposite directions, eventually become unstable in favor of one rotating wave in the non-linear regime. With no azimuthal velocity in the base flow (Re ¼ 0), the matrices in the eigenvalue problem have real coefficients.…”
Section: B Linear Stability Analysismentioning
confidence: 99%
“…The latter would correspond to those studied in the half-zone model 46 and discussed in detail in the Rayleigh-Bénard configuration. 47 In both studies the initial standing waves, which result from superposition of the rotating waves traveling in opposite directions, eventually become unstable in favor of one rotating wave in the non-linear regime. With no azimuthal velocity in the base flow (Re ¼ 0), the matrices in the eigenvalue problem have real coefficients.…”
Section: B Linear Stability Analysismentioning
confidence: 99%
“…(20) In this expression m is related to the number of half wavelengths of the unstable structure (sine or cosine as appropriate) growing in the rescaled domain. Restrictions on k given by condition (20) are replaced in the dispersion relation R = R(k) to provide a dispersion relation R = R(m, Γ ) for each integer m as a function of the aspect ratio Γ . These critical curves for different m are displayed in Fig.…”
Section: Stationary Equations and Linear Stabilitymentioning
confidence: 99%
“…However, recent studies like those of [20,21] suggest that a complete description of the solutions to a convection system may require further analysis. These works address convection problems at constant viscosity with different geometries and have proposed complete nonlinear solutions by combining direct numerical simulations and bifurcation studies based on branch continuation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…One of these two effects can prevail or they can balance each other. 11 The crossing point tends to be at lower P r for increasing Ra. This means that the P r interval, in which the viscous boundary layer would influence the thermal one, increases with Ra.…”
Section: Vertical Profiles and Boundary Layers As Functions Of Ra Andmentioning
confidence: 95%
“…Almost all the pattern-development studies concern convective systems with large aspect ratio (Γ ≫ 1) [9]. For cells of moderate aspect ratio (1 Γ 10) a short review can been found in [11] concerning the work on the first convective states. Through experiments, numerical simulations and theoretical calculations the work just cited mainly provides a stability analysis of convective states.…”
Section: Introductionmentioning
confidence: 99%